DEVELOPMENT OF TEST FOR SYPHILIS - Khramtsov, P.V. (Perm Federal Research Centre Journal, 2015)
Non-instrumental dot blot serological syphilis test based on application of functionalized carbon nanoparticles was developed and optimized. Nitrocellulose membrane sensitized with Treponema pallidum p17 protein served as an immunosorbent. Assay demonstrated 100 % sensitivity and specificity when tested with reference panel of serum. Possibility of detection of antibodies against cardiolipin was also shown.